2015
DOI: 10.5688/ajpe7910149
|View full text |Cite
|
Sign up to set email alerts
|

Practical Team-Based Learning from Planning to Implementation

Abstract: Team-based learning (TBL) helps instructors develop an active teaching approach for the classroom through group work. The TBL infrastructure engages students in the learning process through the Readiness Assessment Process, problem-solving through team discussions, and peer feedback to ensure accountability. This manuscript describes the benefits and barriers of TBL, and the tools necessary for developing, implementing, and critically evaluating the technique within coursework in a user-friendly method. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
17

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 19 publications
1
28
0
17
Order By: Relevance
“…It seems relevant to highlight that in this first meeting, since TBL teaching was new for both professor and students, they decided that if the expectations were not met or the method was considered confusing, both sides could ask for a revision of the teaching-learning process at any time. The model adopted was based on the experience reported by Livingston and co-workers [17] and planned according to Whitley [18].…”
Section: Phases Of the Experimentsmentioning
confidence: 99%
“…It seems relevant to highlight that in this first meeting, since TBL teaching was new for both professor and students, they decided that if the expectations were not met or the method was considered confusing, both sides could ask for a revision of the teaching-learning process at any time. The model adopted was based on the experience reported by Livingston and co-workers [17] and planned according to Whitley [18].…”
Section: Phases Of the Experimentsmentioning
confidence: 99%
“…When groups disagree about best answers, the facilitator instructs the group with the correct answer to teach the other groups; i.e., near-peer teaching. 5 After determining participants' understanding of the material, the facilitator addresses any issues needing clarification. In the application phase learners can practice using cases illustrating the topic presented (e.g., Kreb's cycle as it relates to the patient with diabetic ketoacidosis) and/or standardized learners.…”
Section: Team Based Learningmentioning
confidence: 99%
“…Cognitive psychology has shown that facts and concepts are best recalled when they are taught, practiced, and assessed in the context in which they will be used. 2 Pluta et al describes a shift into a "new era" of learning that employs a diversity of approaches to support collaborative learning. 3 Concomitantly, new teaching styles have evolved to stimulate such learning.…”
mentioning
confidence: 99%
“…최근 미국의 의학협회(the Institute of Medicine)와 약학교육협회(ACPE) 및 세계보건기구 (WHO)와 같은 여러 의료분야 단체에서는 다양한 배경을 가진 전문가의 협업을 강화하고 있다 (Whitley et al, 2015). 이에 발맞춰 의료분야 대학교육에서 문제중심학습이나 팀 기반 학습과 같이 소집단의 상호작용을 중심으로 진행되는 학습자 중심 교육 방법을 통해 의료인에게 필요 한 역량을 증진하려는 노력이 활발하게 적용되고 있다 (Rezaee, Moadeb, & Shokrpour, 2016 (Shin, & Park, 2012).…”
Section: ⅰ 서론unclassified